THEORETICAL FOUNDATIONS FOR THE STUDY OF THE TIMURID PERIOD (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the study of the history of the era of Amir Temur and the Timurids during the years of independence, scientific research conducted in this direction, and new approaches in historiography. The study highlights the scientific significance of the main written sources of the Timurid period, including the works of Sharafuddin Ali Yazdi, Nizomiddin Shami, and Zahiriddin Muhammad Babur. Also, the activities of scientific centers aimed at studying the history of the Timurids during the period of independence, the main results of modern research and their role in the restoration of national history were evaluated. The article reveals the importance of the political, cultural, and spiritual heritage of the era of Amir Temur and the Timurids in restoring historical memory and educating the younger generation in the spirit of patriotism. The results of the study serve to further study the history of the Timurid period and enrich existing views in historiography.
Keywords: Amir Temur, Timurid era, Timur studies, historiography, years of independence, national statehood, historical sources, Zafarnama, Baburnama, scientific research, cultural heritage, historical memory, patriotism, history of Uzbekistan, national identity.